AKTIVITAS ANTIBAKTERI DAN SIFAT ORGANOLEPTIK YOGURT SUSU JAGUNG MANIS DENGAN PENAMBAHAN SUKROSA - sapti widiningsih; joko teguh isworo (Jurnal Pangan dan Gizi, 2011)
Sweet corn milk yogurt with the addition of sucrose is one of the fermentation product of lactic acid bacteria. The purpose of this study was to determine the effect of adding sucrose to the antibacterial activity and organoleptic properties. This study uses a single factor completely randomized design with repeated 4 times, the materials used are sweet corn, plain yogurt, skim milk and sucrose concentrations 0%, 1%, 2%, 3% and 4%. The variables measured were the antibacterial activity using diffusion test and organoleptic properties to the assessment of test scoring panelists. Results showed was significant of adding sucrose to the antibacterial activity of E. coli (8.91 mm) and Salmonella thyphi (9.99 mm). Cs Not significantly of the organoleptic test on fragrance, color and viscosity, however the highest score of sweet corn milk yogurt on the addition of 4% sucrose.